Pengaruh Ragam Mata Pencaharian Dan Tingkat Pendidikan Orang Tua Terhadap Motivasi Belajar Siswa Di PKBM YASPIMIDA Kecamatan Kebonpedes Kabupaten Sukabumi - Samsul Aripin; Istikhori Istikhori; Endin Nasrudin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
From the opinion of experts, it can be concluded that students' learning motivation is influenced by various internal and external factors, and these factors can vary depending on the theory and approach used. Therefore, it is important for educators and educational institutions to pay attention to the factors of Variety of Livelihoods and the Education Level of Parents which can affect Student Learning Motivation and develop learning strategies that can increase student motivation. The research approach used is a quantitative approach. The quantitative approach is the oldest method in research with empirical, objective, structured, rational and systematic characteristics with a research sample of 100 respondents, data collection was taken using a questionnaire. Based on the results of the hypothesis, it states that the variety of livelihoods has a significant influence on student learning motivation in PKBM Yaspimida, Kebonpedes District, Sukabumi Regency. Based on these results, it can be concluded that environmental factors such as the variety of livelihoods and the educational level of parents influence student learning motivation in PKBM YASPIMIDA, Kebonpedes District, Sukabumi Regency. Therefore, efforts need to be made to increase parents' awareness of the importance of supporting their children's learning motivation, especially for families who have a limited variety of livelihoods and low levels of education. This conclusion shows that both the variety of parents' livelihoods and the education level of parents have a significant role in influencing student learning motivation in PKBM YASPIMIDA, Kebonpedes District, Suakabumi Regency. These results indicate the importance of paying attention to these factors in increasing student motivation. The implication is that efforts need to be made to provide support and coaching to students with a variety of livelihoods and parents' educational levels that vary, so as to increase their learning motivation.